Implementation of Good Governance in Poverty Alleviation in Maja District, Majalengka Regency - Rifqi Khairul Arifin; Regan Vaughan; Andre Ariesmansyah (West Science Social and Humanities Studies, 2024)
This study aims to analyze the application of good governance principles in poverty reduction in Maja District, using a qualitative approach. Through in-depth interviews with government officials and relevant stakeholders, this research explores the five main dimensions of good governance: rule of law, transparency, equality, effectiveness and efficiency, and accountability. The results show that upholding the rule of law is critical to ensuring fairness in the distribution of social assistance. The Maja sub-district government has conducted regular monitoring and evaluation to maintain transparency in the use of funds, as well as involving law enforcement agencies in supervision. Transparency of information to the community is also sought through various communication channels, so that the community can actively participate in the decision-making process. In addition, this study identified challenges such as nepotism and differences in poverty data between agencies that can interfere with program effectiveness. Thus, this study concludes that multi-stakeholder collaboration and a systematic approach to monitoring and evaluation are key to improving the effectiveness of poverty reduction programs in Maja District. This research is expected to provide recommendations for policy development that is more inclusive and responsive to community needs.